A Review of the Pathophysiology and Novel Treatments for Erectile Dysfunction - George F. Lasker; Jason H. Maley; Philip J. Kadowitz (Advances in Pharmacological Sciences)
Erectile dysfunction (ED) affects up to 50% of men between the ages of 40 and 70. Treatment with PDE-5 inhibitors is effective in the majority of men with ED. However, PDE-5 inhibitors are not effective when levels of nitric oxide (NO), the principle mediator of erection, are low. The pharmacologic actions of three new potential treatments for ED are discussed in this paper: (1) sGC stimulators/activators, (2) Rho-kinase inhibitors, and (3) sodium nitrite.